Aspectos ecológicos e comportamental de vagalumes Bicellonycha lividipennis motschulsky, 1854 (Coleoptera: Lampyridae) em áreas sob influência de iluminação artificial de vapor de sódio no município de Sorocaba-SP - Mariano, Raone dos Reis (Universidade Federal de São Carlos, 2022)
The consequences of light pollution are reflected between vertebrates and invertebrates. One of the most affected organisms and target of study in this work are fireflies, especially lampyrids. The bioluminescence of these coleopterans is essential for carrying out their biological functions, mainly for inter and intraspecific communication. The present work verified the occurrence of Bicellonycha lividipennis Motschulsky, 1854 of the Lampyridae family, in swamp areas of Sorocaba-SP and region, with points affected or not by light pollution. Unlike other lampyrids, adults of this species persist in areas exposed to relatively high levels of artificial lighting (0.8-8.6 Lux) from a sodium vapor lamp. The twilight spectral overlap at the time of its activity, in contrast to the peak emission of the bioluminescence spectrum, may explain the smaller effect of sodium lamp lighting on this firefly. The results indicate that artificial lighting of Sodium vapor is less impactful to active fireflies at twilight. The beginning of these fireflies' activity during twilight, when there are still high levels of natural lighting, as well as the partial overlapping of the twilight ambient lighting spectra and artificial sodium lighting, explain the lower effect of lighting this type of sodium lamp. in firefly activity and occurrence.
Ecological and behavioral aspects of fireflies Bicellonycha lividipennis motschulsky, 1854 (Coleoptera: Lampyridae) in areas under the influence of sodium vapor artificial lighting in the municipality of Sorocaba-SP
Keywords: Poluição Luminosa; Vagalumes; Lampyridae; Bioluminescência; Impactos Ambientais; Environmental Impacts; Bioluminescence; Light Pollution; Fireflies; CIENCIAS BIOLOGICAS